THE EFFECT OF PERCEPTIONS OF EASE, USEFULNESS, AND TRUST ON THE INTEREST IN USING ACCOUNTING INFORMATION SYSTEMS AMONG TIKTOK SHOP BUSINESS OPERATORS IN THE CITY OF SUKABUMI - Azzahra, Ghefira Nuramalia; Hardianto, Ade Manggala; Firizkiansah, Angge; Muchsam, Yoki; Novitasari, Yuli (International Journal of Multidisciplinary Research and Literature, 2026)
This study aims to analyze the effect of perceived ease of use, perceived usefulness, and trust on interest in using AIS and to answer how these three factors influence business actors' decisions to adopt the system. The study uses a quantitative approach with a survey design involving 140 respondents selected through purposive sampling, a 1-5 Likert-scale questionnaire, and multiple linear regression analysis. The results show that perceived ease of use and perceived usefulness have positive, significant effects on interest in using the system, with p-values of 0.000 and 0.002, respectively. Meanwhile, trust had no effect, with a significance value of 0.591. However, the three variables also had a significant impact on interest in using the accounting information system, as indicated by the F test (p = 0.000). These findings contribute to a stronger understanding of technology acceptance factors and provide a practical basis for business practitioners and system developers to improve the system's ease of use and benefits, thereby increasing user interest.